Heart rate reserve effects on brain activation and cognitive-motor performance while doing an instrumented trail walking task in middle-aged to older adults - Alka Bishnoi; Manuel E. Hernandez (Archives of Gerontology and Geriatrics Plus)
Heart rate reserve (HRR) has been associated with cardiovascular risk in older adults. Previous studies have shown a decrease in HRR associated with decrease in motor and cognitive function in older adults while doing Stroop walking task. However, the link between HRR and changes in cognitive-motor function while dual tasking merit needs further exploration. The objective of this study was to evaluate the effects of HRR on prefrontal cortex (PFC) activation and on cognitive-motor performance during instrumented trail walking task (TWT). We hypothesized that there will be an increase in PFC activation and better cognitive-motor performance with increase in HRR during TWT. This cross-sectional study included 30 middle-aged to older adults who walked at a comfortable walking speed on an instrumented treadmill. Functional near-infrared spectroscopy was used to quantify relative PFC oxyhemoglobin (HbO2) and deoxyhemoglobin (Hb) levels. Cognitive performance calculated using error rate (ER) and motor performance calculated using stride length (SL), stride width (SW), stride time (ST). A linear mixed effect was conducted to investigate the effects of HRR, task, and their interaction on primary measures after controlling for covariates. Our results showed that HbO2 and Hb levels differed significantly, showing increases in PFC activation, i.e. higher HbO2 and lower Hb during TWT with increase in HRR. This increase in PFC activation was associated with increased speed and higher cognitive-motor performance, suggesting these tasks can distinguish changes in automaticity in adults with varying HRR. We also found a decrease in ST association with a higher HRR.